From legal assistance to automated authority: a critical discourse analysis of generative AI in Indonesian digital legal services - Refai (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Indonesia’s expanding digital legal-service ecosystem has brought generative AI into public-facing legal assistance, yet its authority is increasingly produced through platform discourse before its professional, ethical, and regulatory boundaries are fully settled. Objective: This study aims to examine how generative AI is represented in Indonesian digital legal services and how such representation shifts AI from a tool of legal assistance toward a form of automated authority. Method: Using critical discourse analysis, this study analyses 27 publicly accessible documents consisting of platform pages, app descriptions, professional media articles, legal-policy documents, and regulatory-context materials. Results: Findings show that AI authority is constructed through professional research vocabulary, efficiency claims, innovation narratives, access-to-justice language, and references to regulatory accountability. Findings also indicate that users are positioned as self-service legal actors whose access to law is mediated by platform interfaces, automated summaries, guided consultation, and document-generation tools. Implication: Findings further reveal that accountability is unevenly articulated, with legal responsibility often dispersed across professionals, users, ethical soft regulation, data-protection discourse, and platform claims. Novelty: The novelty of this study lies in shifting Indonesian AI-law scholarship from adoption and regulation debates toward the discursive production of automated legal authority.